2013
DOI: 10.1111/mmi.12306
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a serine protease inhibitor which causes inclusion vacuole reduction and is lethal to Chlamydia trachomatis

Abstract: SummaryThe mechanistic details of the pathogenesis of Chlamydia, an obligate intracellular pathogen of global importance, have eluded scientists due to the scarcity of traditional molecular genetic tools to investigate this organism. Here we report a chemical biology strategy that has uncovered the first essential protease for this organism. Identification and application of a unique CtHtrA inhibitor (JO146) to cultures of Chlamydia resulted in a complete loss of viable elementary body formation. JO146 treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 28 publications
6
78
0
Order By: Relevance
“…In H. pylori or C. trachomatis , genomic htrA deletions mutants could not be generated so far. However, functional small molecule inhibitors and substrate-derived peptide inhibitors were designed which efficiently blocked HtrA functions [30, 33, 34]. HtrA-mediated E-cadherin cleavage was also shown for EPEC and S. flexneri supporting our hypothesis that E-cadherin ectodomain shedding might be a prevalent mechanism for pathogenic bacteria to promote virulence through the interference with (baso-) lateral domains of epithelial cells [15].…”
Section: Introductionmentioning
confidence: 93%
“…In H. pylori or C. trachomatis , genomic htrA deletions mutants could not be generated so far. However, functional small molecule inhibitors and substrate-derived peptide inhibitors were designed which efficiently blocked HtrA functions [30, 33, 34]. HtrA-mediated E-cadherin cleavage was also shown for EPEC and S. flexneri supporting our hypothesis that E-cadherin ectodomain shedding might be a prevalent mechanism for pathogenic bacteria to promote virulence through the interference with (baso-) lateral domains of epithelial cells [15].…”
Section: Introductionmentioning
confidence: 93%
“…In addition, it has been reported that HtrA is crucial for the virulence of numerous bacterial pathogens such as Yersinia enterocolitica [41], Salmonella enterica [42], Klebsiella pneumonia [43], Shigella fl exneri [44], Listeria monocytogenes [45], and Chlamydia trachomatis [46]. It is wellknown that HtrA is critical for stress tolerance and survival of most bacteria, because it degrades and prevents aggregation of periplasmic proteins that can misfold under stress conditions [31-33], but only a few reports have studied the discrete functions of HtrA protease and chaperone activities during infection [27-30].…”
Section: Discussionmentioning
confidence: 99%
“…Activitybased probes have been designed to detect a number of bacterial proteins, such as sulfatases 85,86 , serine proteases 87 , the cell wall biosynthetic protein MurA 88 , glycoside hydrolases 89 , redox-sensitive proteins 90,91 and histidine kinases 92 ; however, most of these probes have been used only in gel-based analyses. One additional strategy that has been applied to bacterial imaging is the use of a probe that becomes fluorescent upon turnover by nitroreductase.…”
Section: Additional Small-molecule Probesmentioning
confidence: 99%